2009
DOI: 10.1038/ajg.2009.506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Measurement of Esophageal Acid Exposure Close to the Gastroesophageal Junction on Diagnostic Accuracy and Event-Symptom Correlation

Abstract: Compared with the traditional location, measurement of acid reflux 1 cm above the GEJ improved the diagnostic accuracy as well as symptom correlation in EE, but not in NERD patients. Thus, pH monitoring 1 cm above the GEJ for improving the diagnosis of NERD cannot be recommended in clinical practice at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
10
0
2
Order By: Relevance
“…The 4‐electrode pH monitoring system described in this study can record simultaneously the pH of the distal esophagus, the upper border of the LES, the gastric fundus, and the gastric body. The site of the electrode in the upper border of the LES in this study was quite close to the monitoring site for short‐segment reflux . In patients with GERD, simultaneous monitoring of the pH in the upper border of the LES detected short‐segment reflux in 80% of the patients with normal EAE in the distal esophagus, indicating that synchronous pH monitoring of the very distal esophagus may enhance the diagnostic yield of acid exposure in patients with GERD.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The 4‐electrode pH monitoring system described in this study can record simultaneously the pH of the distal esophagus, the upper border of the LES, the gastric fundus, and the gastric body. The site of the electrode in the upper border of the LES in this study was quite close to the monitoring site for short‐segment reflux . In patients with GERD, simultaneous monitoring of the pH in the upper border of the LES detected short‐segment reflux in 80% of the patients with normal EAE in the distal esophagus, indicating that synchronous pH monitoring of the very distal esophagus may enhance the diagnostic yield of acid exposure in patients with GERD.…”
Section: Discussionsupporting
confidence: 61%
“…Abnormal EAE in the upper border of the LES was defined as the percentage of the time when the pH <4 (over 10.6% according to the studies of Wenner et al . and Bansal et al …”
Section: Methodsmentioning
confidence: 99%
“…Numerous case-control studies have shown that individuals with GERD are 6–8 times more likely to have BE, and the propensity to develop BE increases with more severe symptoms (see Table 1) 2729 Longer duration of GERD may create an environment conducive to the development of BE 30 However, the presence of reflux symptoms is neither sensitive nor specific for pathologic acid reflux 31, 32 , and indeed symptom severity does not correlate well with BE risk. 33, 34 Some work has suggested that patients with more significant symptoms may be less likely to have BE, 35 perhaps because of impaired acid sensitivity of the columnar metaplasia compared to normal squamous epithelium.…”
Section: Epidemiology Of Barrett’s Esophagusmentioning
confidence: 99%
“…In these studies, healthy asymptomatic patients demonstrated good tolerability. 15,16 Dual distal deployment reinforced evidence that a gradient of pH and percentage time pH \4 exists in asymptomatic volunteers. The degree of reflux and percentage time pH \4 decreases at sites farther from the SCJ.…”
Section: Discussionmentioning
confidence: 88%